SENI KRIYA ANTARA TEKHNIK DAN EKSPRESI - Rispul Rispul (Institut Seni Indonesia Yogyakarta, 2012)
The art craft is one of the traditional arts that could be used as an expression medium foranybody. With its capacity as an art filled of local genius, the art craft keep changing in everyaspect, including on creating process and the medium has been used. Combination betweentechnique and proper medium will create the art craft that capable to fulfill the world’s needand demand. Craftsman capability to manage the medium, understanding it, createdinnovatively and to be able to see society’s phenomenon will definitely generate responsiblywork of art. Especially if they can took advantage of local genius that filled with sophisticatedtraditional value during their creating process, this will creates remarkable works of art craftwhich creative and innovative in a fresh form.Keywords: Art craft, technique, expression